Newborn screening for adrenoleukodystrophy: International experiences and challenges - Videbæk, Cecilie; Melgaard, Lars; Lund, Allan M.; Grønborg, Sabine Weller (Molecular genetics and metabolism, 2023)
X-linked adrenoleukodystrophy (XALD) is the most common leukodystrophy. It has an estimated incidence of around 1/17.000, and a variable phenotype. Following the passage of Aidens Law, New York became the first state to implement a newborn screening for XALD in 2013. Since then, 38 American states, Taiwan, and the Netherlands have included XALD in their NBS program, and Japan and Italy have ongoing pilot studies. Screening for XALD allows for early, potentially lifesaving treatment of adrenal insufficiency and cerebral demyelination but is also a complex subject, due to our limited understanding of the natural history and lack of prognostic biomarkers. Screening protocols and algorithms vary between countries and states, and results and experiences gained so far are important for the future implementation of XALD NBS in other countries. In this review, we have examined the algorithms, methodologies, and outcomes used, as well as how common challenges are addressed in countries/states that have experience using NBS for XALD. We identified 14 peer-reviewed reports on NBS for XALD. All studies presented methods for detecting XALD at birth by NBS using a combination of mass spectrometry and ABCD1 gene sequencing. This has allowed for early surveillance of presymptomatic XALD patients, and the possibility for early detection and timely treatment of XALD manifestations. Obstacles to NBS for XALD include how to deal with variants of unknown significance, whether to screen females, and the ethical concerns of an NBS for a disease where we have limited understanding of natural history and phenotype/genotype correlation.